Characterization With KRAS Mutant Is a Critical Determinant in Immunotherapy and Other Multiple Therapies for Non-Small Cell Lung Cancer - Shen, Mo; Qi, Rongbin; Ren, Justin; Lv, Dongqing; Yang, Haihua (Frontiers in Oncology, 2022)
Lung cancer is a frequent type of cancer, which is mainly characterized clinically by high aggressiveness and high mortality. KRAS mutations are among the most frequent in lung cancer patients. In particular, in NSCLC the KRAS oncoprotein is the most common molecular protein detected, accounting for 25% of all oncogenic mutations. Constitutive activation of the KRAS oncoprotein triggers an intracellular cascade in cancer cells, leading to unlimited proliferation of cancer cells and aberrant cell survival states. The results of multiple clinical trials have shown that different KRAS mutation subtypes exhibit different sensitivities to different chemotherapy regimens. Meanwhile, anti-angiogenic drugs have shown differential efficacy for different subtypes of KRAS mutated lung cancer. It was explored to find that the specificity of KRAS mutation subtype would affect PD-L1 expression, so immunotherapy would be of potential clinical value for the treatment of some types of KRAS mutations. It was discovered that the specificity of the KRAS mutation affected PD-L1 which opened up immunotherapy as a potential clinical treatment option. After long-term efforts, the preliminary test data of many early clinical trials show that it is possible to directly inhibit KRAS G12C mutation, which has been proved to be a targeted treatment that is suitable for about 10-12% of patients with advanced NSCLC, having a significant impact on the prolongation of their survival and the improvement of their quality of life. This article reviews the latest progress of treatments for NSCLC with KRAS mutation, in order to gain insight into the biological diversity of lung cancer cells and their potential clinical implications, thereby enabling individualized treatment for patients with KRAS-mutant NSCLC.